2018
DOI: 10.1038/s41598-018-31492-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of dietary fibres on colonic barrier function in elderly individuals with gastrointestinal symptoms

Abstract: Gastrointestinal problems are common in elderly and often associated with psychological distress and increased levels of corticotrophin-releasing hormone, a hormone known to cause mast cell (MC) degranulation and perturbed intestinal barrier function. We investigated if dietary fibres (non-digestible polysaccharides [NPS]) could attenuate MC-induced colonic hyperpermeability in elderly with gastrointestinal (GI) symptoms. Colonic biopsies from elderly with diarrhoea and/or constipation (n = 18) and healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 60 publications
2
21
0
Order By: Relevance
“…Mann-Whitney U-tests), no significant differences were found in colonic permeability as measured by the 5-24 h urinary S/E ratio between elderly and young adults neither in healthy individuals, nor in IBS patients. These findings are largely in line with the comparable 5-24 h urinary S/E ratios between elderly without GI symptoms and younger healthy individuals and as shown by Ganda Mall et al 14 . However, parametric, multivariable linear regression analyses showed that healthy elderly had on average a significantly higher 5-24 h urinary S/E ratio compared with healthy young adults.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Mann-Whitney U-tests), no significant differences were found in colonic permeability as measured by the 5-24 h urinary S/E ratio between elderly and young adults neither in healthy individuals, nor in IBS patients. These findings are largely in line with the comparable 5-24 h urinary S/E ratios between elderly without GI symptoms and younger healthy individuals and as shown by Ganda Mall et al 14 . However, parametric, multivariable linear regression analyses showed that healthy elderly had on average a significantly higher 5-24 h urinary S/E ratio compared with healthy young adults.…”
Section: Discussionsupporting
confidence: 91%
“…Gene name www.nature.com/scientificreports www.nature.com/scientificreports/ were not significantly different between elderly and young adults. To our knowledge, one other study compared sigmoid biopsies of elderly with GI symptoms versus young healthy controls, and found no significant difference in TEER, although fluorescein flux and horseradish peroxidase (HRP) were significantly higher in elderly with GI symptoms compared with healthy controls 14 . Unfortunately, no biopsies of IBS patients were available for Ussing chamber experiments.…”
Section: Clustermentioning
confidence: 89%
See 1 more Smart Citation
“…The concentration of soluble dietary fiber and insoluble dietary fiber were 1.4% and 26.1% in DFRB, respectively (measured value of the present study). Ingredients of DFRB usually increase beneficial bacteria, reduce potentially pathogenic bacteria populations, and improve gut barrier function [10][11][12][13]. Some studies have indicated that addition of rice bran in diets may have a prebiotic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of 10% rice bran improved feed utilization efficiency and tended to increase intestinal Bifidobacteria in weaning pigs [14]. Arabinoxylan (insoluble dietary fiber) reduced colonic mucosa permeability of healthy humans [11].…”
Section: Introductionmentioning
confidence: 99%